2019
DOI: 10.2478/lpts-2019-0018
|View full text |Cite
|
Sign up to set email alerts
|

Impact Modelling of Explosion of Mixture Explosive Charges on the Environment

Abstract: The present paper provides the modelling of the explosion of the charges of the traditional (trotyl) and new blended explosive substances: polymix GR1/8 (74 %) + KRUK2 (26 %), compolite GS6, polymix GR4-T10. As a result of the research, it has been established that when using TNT a specific impulse is formed, which is by 40 % more than an explosion of new mixed explosives, and the safe distance from the source of the explosion of such explosives is increased by 25 %–50 %. On the basis of the established depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…Let the charge detonates instantly and the same average pressure is established throughout its volume , and the density of the explosion products is equal to the initial density of the explosive substance. The movement of soil explosion products is described by the laws of conservation of momentum, mass and internal energy, which for the explosion of a cylindrical charge have the form [7][8]:…”
Section: Mathematical Simulation Of the Explosive Impact On The Soil ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Let the charge detonates instantly and the same average pressure is established throughout its volume , and the density of the explosion products is equal to the initial density of the explosive substance. The movement of soil explosion products is described by the laws of conservation of momentum, mass and internal energy, which for the explosion of a cylindrical charge have the form [7][8]:…”
Section: Mathematical Simulation Of the Explosive Impact On The Soil ...mentioning
confidence: 99%
“…For detonation products S i =0. The relations are performed for the components of the strain rate tensor: (7) The expansion of the explosion products occurs according to the binomial is entropy, i.e (8) The constant values А, В, n0, γ0in ratio (8) are calculated unambiguously based on the known characteristics of explosives [9].…”
Section: Mathematical Simulation Of the Explosive Impact On The Soil ...mentioning
confidence: 99%
“…Therefore, the most important and essential indicators that we propose to use to assess the risks of the demined territories are the following: demining of territories; efficiency of demining and disposal of remnants of military equipment, mines, etc. ; safety and efficiency of demining and disposal technologies; degree of contamination of demined territories after demining and disposal [5-8]; level of safety assessment of the population living in these territories; return of vital infrastructure [5][6][7][8][9][10][11][12][13].…”
mentioning
confidence: 99%
“…• Return of vital infrastructure (х6) -60. It can be concluded that the most important indicator with a high severity of impact (RPN > 125) is the demining of territories [9][10][11][12][13]. It should be noted that it is difficult for specialists to assess the degree of contamination of the contaminated territories in terms of sanitary and epidemic hazards and the degree of danger to the population living in these territories.…”
mentioning
confidence: 99%